2019
DOI: 10.1111/ele.13204
|View full text |Cite
|
Sign up to set email alerts
|

Foraging efficiency and size matching in a plant–pollinator community: the importance of sugar content and tongue length

Abstract: A long‐standing question in ecology is how species interactions are structured within communities. Although evolutionary theory predicts close size matching between floral nectar tube depth and pollinator proboscis length of interacting species, such size matching has seldom been shown and explained in multispecies assemblages. Here, we investigated the degree of size matching among Asteraceae and their pollinators and its relationship with foraging efficiency. The majority of pollinators, especially Hymenopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 52 publications
(107 reference statements)
4
111
0
Order By: Relevance
“…Bronstein and G. Davidowitz, unpublished data). Even if the visitor can access nectar, morphological mismatches between flower and visitor may reduce the efficiency of foraging (Klumpers, Stang, & Klinkhamer, 2019). Even if the visitor can access nectar, morphological mismatches between flower and visitor may reduce the efficiency of foraging (Klumpers, Stang, & Klinkhamer, 2019).…”
Section: Body Size and Feeding Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Bronstein and G. Davidowitz, unpublished data). Even if the visitor can access nectar, morphological mismatches between flower and visitor may reduce the efficiency of foraging (Klumpers, Stang, & Klinkhamer, 2019). Even if the visitor can access nectar, morphological mismatches between flower and visitor may reduce the efficiency of foraging (Klumpers, Stang, & Klinkhamer, 2019).…”
Section: Body Size and Feeding Morphologymentioning
confidence: 99%
“…As many flowers have nectar spurs, deep corollas, or other structures that restrict access to the rewards they offer based on morphology, a pollinator's size and in particular the length of its mouthparts can determine which flowers are successfully visited, the pollination services provided to the plant, and the handling efficiency of the pollinator (Nilsson, 1988). Even if the visitor can access nectar, morphological mismatches between flower and visitor may reduce the efficiency of foraging (Klumpers, Stang, & Klinkhamer, 2019). It will also potentially reduce the quality of pollen transfer, as it will affect the likelihood that the same part of the pollinator's body contacts both the anthers and the stigma.…”
Section: Body Size and Feeding Morphologymentioning
confidence: 99%
“…As a consequence, individuals in populations with smaller plants may be visited less frequently. Several studies have found that plant phenotype is highly predictive of pollination visitation networks (Biddick & Burns, ; Klumpers, Stang, & Klinkhamer, ). For example, Biddick and Burns () demonstrated that plant species with large flowers received higher visitation rates from birds than plants with smaller flowers.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, individuals in populations with smaller plants may be visited less frequently. Several studies have found that plant phenotype is highly predictive of pollination visitation networks Klumpers, Stang, & Klinkhamer, 2019 Another plausible explanation for geographic variation in B. ringens phenotype is that it is driven by features of the abiotic environment, either as plastic responses or as evolved responses to local conditions. However, we found no relations between the most limiting resources (N, P, rainfall) in the Cape (see Cramer, West, Power, Skelton, & Stock, 2014) and perch size.…”
Section: Why Do Babiana Ringens Floral and Inflorescence Phenotypesmentioning
confidence: 99%
“…Interest in flower nectar production is currently increasing and research is aimed at achieving very diverse goals: these include the evolution of plantpollinator interactions (e.g. Nepi et al, 2008;Klumpers et al, 2019;Parachnowitsch et al, 2019), predictive effects of climate changes (e.g. Phillips et al, 2018;Takkis et al, 2018), conservation of endangered species (e.g.…”
Section: Introductionmentioning
confidence: 99%